Conversational humour and (im)politeness a pragmatic analysis of social interaction - Sinkeviciute, Valeria (Topics in humor research ;, 2019)
"Conversational Humour and (Im)politeness is the first systematic study that offers a socio-pragmatic perspective on humorous practices such as teasing, mockery and taking the piss and their relation to (im)politeness. Analysing data from corpora, reality television and interviews in Australian and British cultural contexts, this book contributes to cross-cultural and intercultural research on humour and its role in social interaction. Although, in both contexts, jocular verbal practices are highly valued and a positive response - the 'preferred reaction' - can be expected, the conceptualisation of what is seen as humorous can vary, especially in terms of what 'goes too far'. By examining how attempts at humour can occasion offence, presenting a distinction between 'frontstage' and 'backstage' perceptions of jocularity and looking at how language users evaluate jocular behaviours in interaction, this study shows how humour and (im)politeness are co-constructed and negotiated in discourse. This book will be of interest to scholars and students in pragmatics, conversational humour, (im)politeness, intercultural communication, discourse analysis, television studies and interaction in English-speaking contexts"--